Transformation of toxic potential of Jatropha curcas (Ratanjyot) into protein source: A mini-review - Shukla, Amit; Singh, Satya Pal; Tiwari, Sakshi (Journal of Advanced Veterinary and Animal Research, 2015)
The production of animal largely depends on supplying of quality feed and proteinaceous supplement to the animals. Jatropha plant can grow in the barren lands, and are used as a source of biodiesel. Besides, the plant may act as a rich proteinaceous source. However, the antinutritional factors present in the seed and seed oil of the plant may hamper the availability and beneficial use of the plant. Curcin and phorbol esters are the major toxic compounds present in the plant; these toxic compounds cause to produce liver and kidney diseases. Detoxification of these toxic compounds by physical and chemical means converting to less toxic seed cake may serve the purpose of using this plant in future as a replacement of costly protein supplement for animals. Therefore, in modern world, it is recommended to utilize the protein source by neutralizing the antinutritional factors. This mini-review describes the updates on how J. curcas can be utilized as a supplementary source of protein for animals by decreasing its toxicity. http://dx.doi.org/10.5455/javar.2015.b82